2016
DOI: 10.1007/s10899-016-9645-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress as an Indicator of Co-Occurring Psychopathology among Treatment-Seeking Disordered Gamblers

Abstract: Disordered gamblers frequently present with concurrent anxiety, depressive, personality, and substance use disorders, which may complicate treatment. Although there is a need for a thorough assessment, some questionnaires may prove lengthy for clients and clinicians. Thus, there is a need for brief screens for identifying co-occurring psychopathology. The present study sought to examine whether a brief, self-report measure of psychological distress could indicate the presence of co-occurring psychopathology am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The characteristics of online board gamers, which we referred to as gambling behaviors and psychological status, include impulsivity, mood, and attention. 7,8 Online gamblers are thought to have an introverted personality and depressed mood. 8 Based on an online survey, which in-cluded 10,838 internet-based poker players, Gainsbury et al 9 reported that internet-based poker players showed a greater tendency to "chase their losses" (i.e., seek to recoup lost bets by increasing their subsequent bets) than were offline gamblers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of online board gamers, which we referred to as gambling behaviors and psychological status, include impulsivity, mood, and attention. 7,8 Online gamblers are thought to have an introverted personality and depressed mood. 8 Based on an online survey, which in-cluded 10,838 internet-based poker players, Gainsbury et al 9 reported that internet-based poker players showed a greater tendency to "chase their losses" (i.e., seek to recoup lost bets by increasing their subsequent bets) than were offline gamblers.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Online gamblers are thought to have an introverted personality and depressed mood. 8 Based on an online survey, which in-cluded 10,838 internet-based poker players, Gainsbury et al 9 reported that internet-based poker players showed a greater tendency to "chase their losses" (i.e., seek to recoup lost bets by increasing their subsequent bets) than were offline gamblers. In a review of internet-based poker, factors predictive of excessive internet-based poker playing are suggested to be negative emotions, irrational beliefs, and impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal relation between gambling harm and co-occurring psychological symptoms is not well understood, as there is evidence that psychological symptoms precede the onset of gambling harms (Kessler et al, 2008) and that gambling harms precede psychological symptoms (Afifi et al, 2016; Sundqvist & Rosendahl, 2019). However, it is well established that co-occurring psychological symptoms increase the complexity of clinical presentations (Peter et al, 2016; Pfund et al, 2017; Pietrzak & Petry, 2005).…”
mentioning
confidence: 99%